(3MGTjI Ydi GdahGFO GdVjGFjI aj TQM GdcGajI ddLGejs - (3GddGQj GdCfUGQj, QVj GdOjf, YHO GdZahQ Hf UdGM, (B912 (3g`s
(3ChdgG (B:s
(3bhdg(B: (3GdMeO eUOQ GdeYdhe hGddGe ddLfS Ch GdGSJZQGb Cj cd MeO ef GdCRd GdCHO ef Cj MGeO cGf hjMJed Cf jchf eUOQ ddeLghds
(3BNQgG (B:s
(3bhdg(B: (3hLg GdCcKQ Hd Edi BNQg hCf hLg GdHfGA aj PcQ GdQGA bUO GdEeGdI EP gj CeQ eSJMSf hGdeUMM ddEeGdI cSQ GdQGA hgj dG jMUd EdG HJbOjQ GdHfGA dCfg EPG CYQH efY GdUQa ade JcSQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 175s
(3cTa GdXfhf(B: 2 / 1372s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs